Sex and alcohol use disorder predict the presence of cancer, respiratory, and other medical conditions: Findings from the National Epidemiologic Survey on Alcohol and Related Conditions-III. (December 2021) - Verplaetse, Terril L.; Peltier, MacKenzie R.; Roberts, Walter; Burke, Catherine; Moore, Kelly E.; Pittman, Brian; McKee, Sherry A.
Highlights: Drinking has substantially increased in women in recent years compared to men. We aimed to newly examine relationships between sex, AUD, and past year medical conditions using NESARC-III. Women were 1.5 times more likely to be diagnosed with a past medical condition vs. men. Women with AUD were 2 times more likely to report respiratory illness and cancers compared to men with AUD. Effective interventions for a broad spectrum of medical conditions should consider the role of problematic alcohol use. Abstract: Background: Women experience greater health consequences of alcohol compared to their male counterparts. In recent years, rates of drinking and heavy alcohol use have increased in women while remaining relatively steady in men. Thus, our aim was to newly examine associations between sex, AUD, and the presence of medical conditions in a large nationally representative, cross-sectional dataset. Methods: Using data from the U.S. National Epidemiologic Survey on Alcohol and Related Conditions (NESARC-III; n = 36, 309), we evaluated relationships among sex and DSM-5 AUD, and their association with past year clinician-confirmed medical conditions. Results: Women were 1.5 to 2 times more likely to be diagnosed with a past year cancer, pain, respiratory, or other significant medical condition compared to men ( odds ratio [ OR ] = 1.331–2.027). Individuals with an ongoing DSM-5 AUD were nearly 1.5 to 2 times more likely to report a confirmed past year liver, cardiovascular, cancer, or other significant medical condition compared to those without an AUD ( OR  = 1.437–2.073). Interactive effects demonstrated that women with an ongoing AUD were 2 to 3 times more likely to report a past year doctor- or health professional-confirmed medical condition compared to men; specifically, respiratory conditions and cancers ( OR  = 1.767–2.713). Conclusions: Results identify that AUD is a critical factor associated with disease that spans organ systems. Associations between AUD and respiratory conditions or cancers are particularly robust in women. Effective interventions for a broad spectrum of medical conditions should consider the role of problematic alcohol use, especially given that rates of drinking in women are increasing.